Endosymbionts Alter Larva-to-Nymph Transstadial Transmission of Babesia microti in Rhipicephalus haemaphysaloides Ticks - Li, Lan-Hua; Zhang, Yi; Zhu, Dan; Zhou, Xiao-Nong (Frontiers in Microbiology, 2018)
Maternally inherited endosymbionts inhabit a variety of arthropods. Some of them can protect the arthropod host against a wide range of pathogens. However, very little is known about the association between endosymbionts and pathogen susceptibility in ticks. The present study investigated the effect of endosymbionts on larva-to-nymph transstadial transmission of Babesia microti by Rhipicephalus haemaphysaloides ticks. Engorged female ticks were injected with PBS, ciprofloxacin or kanamycin. The offspring larvae were used to infest B. microti-positive mice. Prevalence of B. microti among the nymphs in different treatment groups and its association with endosymbiont density in the larvae were analyzed. The results showed that the prevalence of B. microti in the kanamycin-treated group (63.9%, 95% confidence interval (CI): 52.8%-75.0%) was higher than that in the PBS- (23.6%, 95% CI: 13.8%-33.4%) or ciprofloxacin-treated (25.0%, 95% CI: 15.0%-35.0%) groups. This increased prevalence was associated with reduced density of Coxiella-like endosymbiont but was not related to the density of Rickettsia-like endosymbiont. No direct evidence has previously been reported about the impact of Coxiella-like endosymbiont on pathogen susceptibility in ticks. This study reveals that endosymbionts are potentially important defensive symbionts of R. haemaphysaloides which may influence the colonization or susceptibility of B. microti in the tick host.